Analysis of Islamic Business Ethics in Tiktok Live Shopping Marketing - Alvi Nuur Rasyidah; Bakhrul Huda (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Tiktok live shopping facilitates buying and selling transactions. This feature has a positive impact on sellers and buyers, including making it easier to get the desired items. On the other hand, this feature also raises debates. One of them is the discrepancy between the product advertised and received by the buyer. This research aims to review tiktok live shopping marketing based on Islamic business ethics theory. This research uses qualitative methods with data sources used through primary data and secondary data. Primary data is taken through interviews and observations and secondary data is taken from (google scholar, publish or perish, morarel), official journal websites and institutional repositories. Based on the research results, tiktok live shopping is not fully in accordance with the principles of Islamic business ethics because the principle of justice or balance has not been fulfilled, the difference in product prices based on consumer behavior algorithms can lead to injustice, therefore the pricing system based on consumer profiles must be explained openly to buyers so that there is no injustice or discrimination that can harm one party.